SHAPE America and physical literacy: an event horizon?. Issue 2 (4th May 2021) - Landi, Dillon; Blackshear, Tara B.; McFadden, Carrie
ABSTRACT: In this paper, we reflect on SHAPE America's K-12 National Standards and its connection to physical literacy. We argue physical educators in the United States have primarily engaged with the term physical literacy without engaging with the theoretical and pedagogical depth of the concept . Despite this, SHAPE America does explicitly endorse an adapted version of Whitehead's definition of the physical literacy concept . In drawing on feminist intersectional thought, we make an argument that SHAPE America's adoption of physical literacy has produced an era of 'disorientation' in United States physical education. Within this disorientation, much of the advancements made in theory, pedagogy, sociocultural issues, as well as curriculum have been lost. We conclude by calling for a revamping of the standards that are not bound to a single concept, model or theoretical paradigm.